Civic Virtue Pada Kegiatan Ekstrakurikuler Palang Merah Remaja - M Yusuf; Yosi Novrinda (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This article aims to find out what the efforts and obstacles to strengthening civic virtue in Youth Red Cross (YRC) extracurricular activities at MAN 1 Indragiri Hilir. This article was conducted through a qualitative approach with a descriptive method. Data was obtained by observation, interview, and documentation methods. The results showed that efforts to strengthen civic virtue in YRC MAN 1 Indragiri Hilir extracurricular activities were carried out in several ways, namely: First, through the activity of delivering material directly by the YRC coach. Second, through a joint exercise between YRC MAN 1 Indragiri Hilir with the Indonesian Red Cross (PMI) Indragiri Hilir Regency. Efforts to strengthen civic virtue in YRC extracurricular MAN 1 Indragiri Hilir still have several obstacles, namely: First, YRC members have difficulty understanding the content because they are not accompanied by direct practice. Second, YRC members cannot participate in regular training either delivered directly by the supervisor or joint activities with PMI Indragiri Hilir regency because the training schedule always coincides with other extracurricular agendas. The limitation of this research is that it has not explored what steps must be taken in order to overcome these obstacles.